Legal and Contract Management Analysis of the Most Frequently Negotiated Contact Terms Among Malaysian Businesses - Shamsuddin, Azura (2010)
The central argument of this thesis is that through the incorporation of proper management and treatment of the organizations’ contractual agreement with respect to their most frequently negotiated contract terms as part of the organizations’ contract management strategy in line with the organizations’ goals, visions and missions would provide the relevant signals that could highlight potential legal issues before they become legal problems. This would enable the organizations to effectively handle legal disputes that may arise in the course of doing business in line with the law. Further, in doing so, the organizations would also be able to attain their core business objectives while minimising risks and creating value at the same time. This thesis therefore, seeks to investigate the operations and effects of contract law, theories and practises with respect to the most frequently negotiated contract terms and how they relate to the contract management strategy of Malaysian business organizations as the social institutions. As there is no existing empirical evidence on the most frequently negotiated contract terms that is representative of Malaysian businesses prior to this thesis, a survey questionnaire was conducted to establish such a profile. The quantitative method used is however, limited to descriptive statistics only as it is not the purpose of this research to find any mathematical answers but rather for the purpose of making generalisation to a population from a sample with respect to the most frequently negotiated contract terms. From the findings of the survey, the top two most frequently negotiated contracts terms i.e. liquidated damages and limitation of liability provisions were selected to be further researched. This involves the analysis of liquidated damages and limitation of liability provisions from both the legal and theoretical perspectives. Thereafter, having due regards to the legal and theoretical positions with respect to liquidated damages and limitation of liability provisions as they stand today, this thesis then analysed the mechanisms on how organizations could better manage these two provisions in particular and the contract in general, from a contract management perspective. Finally,as the coup de grace, this thesis concludes with a few recommendations for legal and management reforms pertaining to the two provisions as well as possible future research that can be taken in the research area.